The Art of Intellegence : Lessons from a Life in the CIA's Clandestine Service - Crumpton, Henery A. (New York Penguin Books, 2013)
A counterterrorism spy describes his leadership of the campaign that routed al Qaeda and the Taliban in the weeks after the September 11 attacks, offering insight into the ways in which the Afghanistan campaign changed American warfare.
Include Index
Keywords: United States -- Intelligence officers -- Intelligence service -- Crumpton, Henry A